AS PERDAS TERRITORIAIS DO ESTADO BOLIVIANO (1825-1935) - Reyes, Fernando Siliano (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2009)
The present study approaches the constitution of the Bolivian State and its territorial losses since its foundation in 1825 until the end of the Chaco War in 1935. Not only did such losses diminish the size of this Bolivian State’s territory but also restrained the country’s circulation perspectives. The country has tried to minimize its losses through international agreements on territorial use with exactly those neighbors which have taken part of its territory.To understand this process, the present study describes Bolivia’s populational and territorial formation, beginning with pre-Colombian peoples, mainly the Quechuas and the Aymaras, followed by the Spanish occupation, taking into account the fact that Bolivia has its own plentiful historicity, and is specifically inserted in the order of the world capital. Last but not least, this paper discusses the successive wars fought against three neighbor countries – Chile, Brazil and Paraguay – which resulted in significant territorial loss to the Bolivian State.